R&D sensitivity to asset sale proceeds: New evidence on financing constraints and intangible investment - Borisova, Ginka; Brown, James R. (Journal of Banking & Finance, 2013)
We examine the intersection between corporate divestitures of tangible assets and investment in intangible capital (R&D) to provide new tests for the impact financing constraints have on real activity. A positive R&D sensitivity to asset sale proceeds indicates binding financing constraints since cash inflows from tangible asset sales are negatively correlated with productivity shocks and not otherwise connected to intangible investment via non-financial channels. Using a variety of estimation approaches, we document a strong, positive link between cash inflows from fixed asset sales and corporate R&D investment, but only among firms most likely facing binding financing constraints. These results offer robust evidence that financing frictions impact the increasingly important yet understudied intangible corporate investments that drive innovative activity, and they highlight a previously unexplored but potentially valuable use of proceeds from fixed asset divestitures.